Overview of the European post‐authorisation study register post‐authorization studies performed in Europe from September 2010 to December 2018. Issue 6 (11th February 2022) - Sultana, Janet; Crisafulli, Salvatore; Almas, Mariana; Antonazzo, Ippazio Cosimo; Baan, Esme; Bartolini, Claudia; Bertuccio, Maria Paola; Bonifazi, Fedele; Capuano, Annalisa; Didio, Antonella; Ehrenstein, Vera; Felisi, Mariagrazia; et al.
Abstract: Background: The European post‐authorisation study (EU PAS) register is a repository launched in 2010 by the European Medicines Agency (EMA). All EMA‐requested PAS, commonly observational studies, must be recorded in this register. Multi‐database studies (MDS) leveraging secondary data have become an important strategy to conduct PAS in recent years, as reflected by the type of studies registered in the EU PAS register. Objectives: To analyse and describe PAS in the EU PAS register, with focus on MDS. Methods: Studies in the EU PAS register from inception to 31st December 2018 were described concerning transparency, regulatory obligations, scope, study type (e.g., observational study, clinical trial, survey, systematic review/meta‐analysis), study design, type of data collection and target population. MDS were defined as studies conducted through secondary use of >1 data source not linked at patient‐level. Data extraction was carried out independently by 14 centres with expertise in pharmacoepidemiology, using publicly available information in the EU PAS register including study protocol, whenever available, using a standardised data collection form. For validation purposes, a second revision of key fields for a 15% random sample of studies was carried out by a different centre. The inter‐rater reliability (IRR) was then calculated. Finally, to identify predictors of primary data collection‐based studies/versus those based on secondary use of healthcare databases) or MDS (vs. non‐MDS), odds ratios (OR) and 95% confidence intervals (CI) were calculated fitting univariate logistic regression models. Results: Overall, 1426 studies were identified. Clinical trials ( N  = 30; 2%), systematic reviews/meta‐analyses ( N  = 16; 1%) and miscellaneous study designs ( N  = 46; 3%) were much less common than observational studies ( N  = 1227; 86%). The protocol was available for 63% ( N  = 360) of 572 observational studies requested by a competent authority. Overall, 36% ( N  = 446) of observational studies were based fully or partially on primary data collection. Of 757 observational studies based on secondary use of data alone, 282 (37%) were MDS. Drug utilisation was significantly more common as a study scope in MDS compared to non‐MDS studies. The overall percentage agreement among collaborating centres that collected the data concerning study variables was highest for study type (93.5%) and lowest for type of secondary data (67.8%). Conclusions: Observational studies were the most common type of studies in the EU PAS register, but 30% used primary data, which is more resource‐intensive. Almost half of observational studies using secondary data were MDS. Data recording in the EU PAS register may be improved further, including more widespread availability of study protocols to improve transparency.